Current account imbalances and adjustment policies: a case study of Saudi Arabia - Al-Nassar, Ahmed Abdulmohsen, author; Ozawa, Terutomo, advisor; Davies, Stephen P., advisor; Phillips, Ronnie, committee member; Kling, Robert, committee member (Colorado State University. Libraries, 2000)
Saudi Arabia has experienced wide variations in export proceeds leading, along with other factors such as government balance and money stock, to sharp fluctuations in its current account balance for the period of 1969-1997 (between 58.7% of the GDP in 1978 and -23.4% of the GDP in 1991). The sharp fluctuations in the current account balance have made it difficult for Saudi planners and policy makers to adopt appropriate economic policies that will promote economic growth. In this study, two approaches have been used to investigate the current account imbalances in Saudi Arabia, in order to assist Saudi planners and policy makers in making appropriate decisions. To determine if the current account imbalances are excessive under the neoclassical assumptions, the intertemporal approach was carried out using the present value of the current account method. The estimation results showed that the model captures the statistically important aspects of the current account behavior for the period of 1969-1997. According to the intertemporal theorists, there is no need for policies to deal with the deficit or the surplus in the Saudi Arabian current account since they are the result of maximization behavior. But since Saudi Arabia's economy has special factors (a single commodity export economy and a high degree of openness of the economy) that may affect the risks associated with running large external deficits, widening external deficits may pose significant risks in the event of unfavorable shocks. For these reasons, the government needs to be on the alert to deal with deterioration in the current account position. The conventional approach was carried out using the vector autoregression (VAR) model to determine the factors that cause the current account variability under the assumptions of the neo-Keynesian theory. The results revealed that the government balance, the money stock and the terms of trade have the greatest impact on the current account. These factors can be managed to deal with the current account imbalances in the short term, but in the long term, a diversification of exports and reforming the labor market are the most important policies that need to be implemented.
Keywords: finance; studies; oil reserves